Effects of pulse cycle number on the quality of pulsed atomic-layer epitaxy AlN films grown via metal organic chemical vapor deposition - Rahman, Mohd Nazri Abd; Sulaiman, Abdullah Fadil; Abdul Khudus, Muhammad Imran Mustafa; Allif, Kamarul; Talik, Noor Azrina; Basri, Siti Hajar; Shuhaimi, Ahmad (IOP Publishing, 2019)
The effect of different numbers of Al and N2 pulse cycles on the quality of AlN films prepared via the pulsed atomic-layer epitaxy (PALE) technique and epitaxially deposited on a c-plane sapphire substrate by metal organic chemical vapor deposition were investigated. The characteristics of AlN/sapphire were studied by atomic force microscopy, field emission scanning electron microscopy and Raman spectroscopy. AlN film deposited with the PALE technique with the highest number of pulse cycles (1050) was observed to exhibit highly uniform spherical AlN grains and a dense film surface with a root mean square roughness of 0.46 nm. Transition of the E2 (high) peak from the Raman spectrum shows that the strain compression in PALE AlN films is inversely proportional to the number of pulse cycles. © 2019 The Japan Society of Applied Physics.